A prática pedagógica investigativa como instrumento metodológico no ensino de luz na educação básica - Gomes, Ingrid Nylla Fontes (2022)
Education is a determining factor in the formation of the individual, because it is through education that the student begins to form his or her identity as a social being. Education takes place through continuous procedures, in which the student is stimulated to make new discoveries. It is at school where children can question, research, use their creativity to solve problems and debate the different answers and questionings with their peers. These, in turn, are guided by a teacher so that at the end of his or her journey he or she will be able to make their own decisions. For this it is necessary that the teacher uses means to reach the student. Although there are several possible subjects, the one chosen was 'Light', a topic that is part of the child's everyday life. Light becomes a subject inside the classroom and when used with an Investigative Pedagogical Practices teaching methodology that produces a better understanding of the teaching-learning processes. In the municipality of Nepomuceno, in Minas Gerais, the Elementary Education teachers of the Escola-Projeto Curumim sought in 2017 to develop the skills of children and teachers in astronomy and astronautics in partnership with the extension project "The magic of physics and the Universe" at UFLA. Over time this partnership has brought several results, specifically in this master's research project, in which the online extension course - "The Investigative Pedagogical Practice as a Methodological Instrument in Teaching Light to Elementary Education Teachers in Curumim", which took place at the time of the Covid-19 pandemic in September 2021, was addressed. The objective of this research is to analyze the construction of investigative pedagogical practices as a methodological tool in teaching light, from these extension classes and the practices of the teachers at Escola-Projeto Curumim. The methodology adopted is based on bibliographic research, qualitative research of the description of the extension course offered, of the classes that were recorded, and of the investigative notebooks of the teachers during the classes. Analyses were made of the theory and investigative teaching practices, of the experiences that were obtained by the teachers and by me throughout my journey as a master's student, and of my experience in the classroom. It was possible to register how the investigative practices using light as an instrument contribute to the autonomy and the construction of scientific knowledge in which the human being is immersed. This makes it plausible to say that using these investigative teaching practices with light helps shape the teaching-learning environment, because they stimulate sensations and emotions. Influencing aspects such as social, motor, psychic and cognitive, thus acting on the motivation and achievement of the students.